(untitled) - Tonias, Demetrios E. (New York, 2007)
Filled with real-world case studies, powerful computer-aided design methods, and over 400 detailed illustrations, the Second Edition of Bridge Engineering features: New cost-effective and highly efficient maintenance and repair methods; The most current AASHTO design codes and ASCE design techniques; Complete integration of LRFD and LFD methods throughout, together with examples and problems; Cutting-edge design and construction methods; SI units integrated throughout for international usage.
Keywords: Bridges,Bridges; Design and construction,Maintenance and repair